Comparison The Property Of Tungsten And Lead For Protection Against Radiotherapy In Different Thickness And Position As Shielding Materials - Tuntiwong, Kuson; Patchanee, Siripatra; Wattanachaiyasit, Suthamat; Kaewbunperm, Urairat (Asian Journal of Medical Research, 2017)
Background: Osteoradionecrosis (ORN) is a late complication of irradiation that does not resolve spontaneous. The aim of this study was to evaluate the effectiveness of holding tungsten and lead position to decrease radiation dose. Methods: The research was performed by using dried skull model covered with paraffin wax representing tissue. The protective devices had 2 models; the first model attached with tungsten or lead sheets (size 2.5x3.5 cm2 12 mm. in thickness), were constructed and placed in the both sides of mandible buccally. The others was similar to the first model, but the difference of it was constructed and placed in the mandible linguo- buccally. The 6 MV (2Gy) of photon was radiated, and then the percentages of remained relative doses in the mandible at different areas were measured. Results: The unshielded dried skull phantom radiation dose average ranged from 2.029 to 3.620 nCb. The first models, the percentage mean of remained relative dose were 67.335% and 46.878% in tungsten and lead respectively. The others were 57.494% and 40.677% in tungsten and lead respectively. The tungsten protective device significantly decreased the percentage mean of transmission dose more than the lead shield (p = 0.05), the percentage mean of transmission dose of both shields was difference significantly in each location (p = 0.05) and the first model shield had significantly difference in compare with the others (p = 0.05), exception in the model 2 was 12 mm. tungsten when right radiation beam entried. Conclusion:The tungsten protective device can decrease the remained doses more than the lead device.The position holding the metals should be the buccally.